High Risk of HBV Infection Among Vaccinated Polytransfused Children With Malignancy. Issue 1 (January 2021) - El-Sayed, Manal H.; Said, Zeinab N.A.; Abo-Elmagd, Enas K.; Ebeid, Fatma S.E.; Salama, Iman I.
Abstract : Aim of the Study: The national Egyptian hepatitis B virus (HBV) vaccination program coverage of all infants started in 1992. The study aimed to assess immunity against HBV and occurrence of HBV breakthrough infections in vaccinated polytransfused children with malignancies. Patients and Methods: Eighty-nine polytransfused children with malignancies were recruited; 37 were on chemotherapy (male:female 20:17; mean age 7.7±4.0 y), and there were 52 naive patients (male:female 31:21; mean age 7.6±3.2 y). In addition, 162 age-matched and sex-matched healthy controls were recruited. Patients' sera were tested for quantitative anti-hepatitis B surface (HBs) (enzyme-linked immunoassays technique), hepatitis B surface antigen (HBsAg), total anti-hepatitis B core, and HBV-DNA (nested polymerase chain reaction for surface, core, and x-regions). Results: There was a significant lower percentage of having protective anti-HBs (10 to 100 IU/L) level among those receiving chemotherapy (13.5%) than those without (44.2%) and controls (32.1%). Twenty-one (67.7%) of those on chemotherapy were HBsAg positive compared with 10 (32.2%) of those without. Overall, 46 patients were HBV-DNA positive; 38 were c-region positive, 5 were s-region positive, 2 positive for the c-region and the s-region, and 1 tested positive for the c-region and the x-region. Of 46 patients, 20 were also positive for HBsAg (overt infection), while 26 had occult HBV infection (HBsAg-negative). Anti-HBs ≥10 IU/L co-existed among 45% of patients with overt infection and in 50% of those with occult infection. There was nonsignificant impact of receiving chemotherapy on the level of HBV-DNA. Conclusions: Vaccinated children with malignancies, especially those under chemotherapy, are at a significant risk of HBV infection. The co-existence of anti-HBs with HBsAg and/or HBV-DNA may represent a possible residual transfusion-transmission risk with mutant HBV strains.